Production of monoclonal antibodies with a controlled N-glycosylation pattern in seeds of Arabidopsis thaliana - Loos, Andreas; Hillmer, Stefan; Robinson, David G. (Plant biotechnology journal, 2011)
Seed-specific expression is an appealing alternative technology for the production of recombinant proteins in transgenic plants. Whereas attractive yields of recombinant proteins have been achieved by this method, little attention has been paid to the intracellular deposition and the quality of such products. Here, we demonstrate a comparative study of two antiviral monoclonal antibodies (mAbs) (HA78 against Hepatitis A virus; 2G12 against HIV) expressed in seeds of Arabidopsis wild-type (wt) plants and glycosylation mutants lacking plant specific N-glycan residues. We demonstrate that 2G12 is produced with complex N-glycans at great uniformity in the wt as well as in the glycosylation mutant, carrying a single dominant glycosylation species, GnGnXF and GnGn, respectively. HA78 in contrast, contains additionally to complex N-glycans significant amounts of oligo-mannosidic structures, which are typical for endoplasmic reticulum (ER)-retained proteins. A detailed subcellular localization study demonstrated the deposition of both antibodies virtually exclusively in the extracellular space, illustrating their efficient secretion. In addition, although a KDEL-tagged version of 2G12 exhibited an ER-typical N-glycosylation pattern, it was surprisingly detected in protein storage vacuoles. The different antibody variants showed different levels of degradation with hardly any degradation products detectable for HA78 carrying GnGnXF glycans. Finally, we demonstrate functional integrity of the HA78 and 2G12 glycoforms using viral inhibition assays. Our data therefore demonstrate the usability of transgenic seeds for the generation of mAbs with a controlled N-glycosylation pattern, thus expanding the possibilities for the production of optimally glycosylated proteins with enhanced biological activities for the use as human therapeutics.